Bluestone concert an historic lesson - Barnes, Rebecca (Raton, NM Raton Range, 1994)
Article is about Robert Bluestone's performance of classical guitar at the Old Pass Gallery.
Newspaper Article + Photograph of Robert Bluestone
Master list item #: 37
File location is in the Raton file Cabinet
Keywords: Bluestone, Robert -- Classical Guitarist; Old Pass Gallery; Music Performance; Renaissance Music; Jazz Music; Raton, New Mexico